Synthesis of spiro quasi[1]catenanes and quasi[1]rotaxanes via a templated backfolding strategy - Luuk Steemers (Nature Portfolio, 2017)
Spiro compounds contain two or more rings linked together through one common atom. Here the authors provide a method to backfold both rings, producing spiro quasi[1]catenanes, via a strategy of temporarily linking the linear intermediates with covalent bonds.